Gender differences in labour market integration trajectories of recently arrived migrants in the Netherlands. Issue 11 (18th August 2018) - Ala-Mantila, Minna; Fleischmann, Fenella
ABSTRACT: This study investigates gender differences in recently arrived migrants' labour market activity and occupational status both shortly after arrival and with increasing length of stay. We examine the role of education, household composition and traditional gender role values by estimating multi-group multilevel models based on three waves of the New Immigrants to the Netherlands Survey. In line with findings regarding gender gaps in labour market behaviour, recent female migrants are less active on labour market than their male counterparts, and we observe a clear motherhood penalty and fatherhood premium on the number of hours worked. Men and women show only marginal differences in their occupational statuses. Changes over time do not differ between men and women, indicating persistent gender inequality in labour market attainment. Moreover, interesting differences between the nationalities were found. Polish migrants show the highest activity levels and lowest occupational status, also when compared to Bulgarians. Spanish migrants hold the highest occupational statuses. Recent Turkish migrants seem to be better integrated and show fewer gender differences than the more established Turkish minority in the Netherlands.